Role of the ER/NO/cGMP Signaling Pathway in the Promotion of Osteogenic Differentiation of Rat Bone Marrow Mesenchymal Stem Cells by Actaea racemosa Extract. (15th November 2016) - Yang, Shenlan; Zhou, Yanping; Shuai, Bo; Zhu, Rui; Xu, Wei; Wu, Yanran; Deng, Danfang; Luo, Yingying
Abstract : Purpose / Objective . To investigate the effect of Actaea racemosa (AR) extract on in vitro osteogenic differentiation of rat bone marrow mesenchymal stem cells (BMSCs) via the ER/NO/cGMP signaling pathway. Methods / Materials . Rat BMSCs were treated with osteogenic differentiation-inducing medium containing AR; estrogen receptor antagonist, ICI 182, 780 (10 −6  mol/L); and nitric oxide synthase inhibitor, L-nitro arginine methyl ester (L-NAME, 6 × 10 −3  mol/L). Markers of osteogenic differentiation (alkaline phosphatase [ALP] activity, osteocalcin secretion, and calcium ion deposit levels) and the levels of key signaling molecules (nitric oxide synthase [NOS], nitric oxide [NO], and cyclic guanosine monophosphate [cGMP]) were assessed. Results . AR (10 −1 –10 −6  g/L) increased ALP activity in a dose-dependent manner, and the highest ALP, osteocalcin, and osteoprotegerin activities were achieved at an AR concentration of 10 −4  g/L. Therefore, the concentration of 10 −4  g/L was used for promoting osteogenic differentiation of BMSCs in subsequent analyses. At this concentration, AR increased the levels of NO and cGMP, and such effects could be blocked by the estrogen receptor antagonist (ICI 182, 780) and nitric oxide synthase inhibitor (L-NAME). Conclusion . AR induced osteogenic differentiation of rat BMSCs through the ER/NO/cGMP signaling pathway. This finding provides the theoretical foundation for the mechanism of AR in the treatment of postmenopausal osteoporosis.